Perioperative Mortality and Long‐Term Survival in 80 Dogs and 32 Cats Undergoing Excision of Thymic Epithelial Tumors. Issue 5 (3rd November 2014) - Garneau, Mark S.; Price, Lori Lyn; Withrow, Stephen J.; Boston, Sarah E.; Ewing, Patty J.; McClaran, Janet Kovak; Liptak, Julius M.; Berg, John
Abstract : Objective: To examine perioperative mortality, long‐term survival, causes of death, and prognostic factors for dogs and cats undergoing surgical excision of thymic epithelial tumors (TETs). Study Design: Multi‐institutional case series. Animals: Eighty dogs and 32 cats. Methods: Follow‐up information was obtained for dogs and cats that underwent surgical excision of a TET between 2001 and 2012. Results: Perioperative mortality was 20% in dogs and 22% in cats. No independent risk factors for perioperative mortality were identified. The estimated median survival time for all dogs was 1.69 years (95% CI 0.56–4.32) and the 1‐ and 4‐year survival rates were 55% (95% CI 44–67) and 44% (95% CI 32–56). The estimated median survival time for all cats was 3.71 years (95% CI 0.56‐unestimatable) and the 1‐ and 4‐year survival rates were 70% (95% CI 53–87) and 47% (95% CI 0–100). Of animals that survived to discharge, 42% of dogs and 20% of cats eventually died of TET‐related causes. The presence of paraneoplastic syndromes (hazard ratio [HR] 5.78, 95% CI 1.64–20.45, P  = .007) or incomplete histologic margins (HR 6.09, 95% CI 1.50–24.72, P  = .01) were independently associated with decreased survival in dogs. No significant predictors of survival were identified in cats. Conclusions regarding the effect of chemotherapy or radiation therapy could not be made. Conclusions: While there is substantial risk of perioperative death in dogs and cats undergoing surgery for TETs, many animals that survive to discharge have prolonged survival. Survival is significantly decreased in dogs with paraneoplastic syndromes or incomplete histologic margins.